Hidden Infection in Asymptomatic Congenital Lung Malformations—A Decade Retrospective Study - Liu, Chenyu; Yu, Xuejiao; Cheng, Kaisheng; Luo, Dengke; Yuan, Miao; He, Taozhen; Xu, Chang (Frontiers in Pediatrics, 2022)
Background: Whether to operate on asymptomatic patients with congenital lung malformations (CLMs) remains controversial. Our study intended to find out the proportion of hidden infection in CLMs and its effect on surgery, to provide help for the management of asymptomatic CLMs patients. Methods: A retrospective review of the medical records of patients with asymptomatic CLMs from January 2011 to December 2020 was performed in our center. Selected asymptomatic patients were divided into a nonhidden infection group (NHI) and a hidden infection group (HI). Results: A total of 581 asymptomatic CLMs patients were included in this study. Thirty-two percent of asymptomatic CLMs patients had hidden infection in the lesion. Among various CLMs diseases, intralobular pulmonary sequestration had the highest percentage of hidden infection (48.8%). With age, the proportion of HI gradually increased. Patients in the HI and NHI groups were 223 and 121. The incidence of pleural adhesion and focal abscess in the HI group were 14.9% and 7.4%, respectively. Statistical significances were shown between the two groups in intraoperative blood loss (p=0.002), operation time (p=0.045), chest tube drainage time (p<0.001), postoperative hospital stay (p<0.001), and air leak (p=0.012). Conclusion: The proportion of HI detected by postoperative pathological results was high and they could increase the difficulty and risk of surgery. Therefore, early surgery may be a more appropriate choice for the management of asymptomatic CLMs patients.